Vertical and horizontal (mis)match of university degrees in the Hungarian labour market - Zsuzsanna Kiss (Humanities & Social Sciences Communications)
Abstract In the fourth industrial revolution, higher education institutions (HEIs) face numerous new challenges. The changing circumstances impact the economy and the labour market, bringing new competencies to the forefront. The employability and labour market success of graduates from higher education institutions is crucial from the perspective of human capital investments, and it is prominently featured as a quality indicator of higher education institutions in global rankings. Employability of HEI graduates is increasingly being monitored. This study examines the horizontal and vertical (mis)match of young graduates in the labour market, focusing on the correspondence between the field and level of qualification, with a specific emphasis on exploring differences across academic disciplines. The analysis is based on data from the 2015 survey of the Graduate Tracking System (DPR) in Hungary. The purpose of the study is to map the vertical and horizontal labour market (mis)match of Hungarian graduates of various scientific fields and to compare them with the results of other countries in order to reveal country-specific characteristics. The novelty of the paper is the expanded interpretation of horizontal fit, which in a multidisciplinary-aspect measures horizontal fit along two indicators, which are convertibility and substitutability. Substitutability shows the relationship between the professional qualification required in the job and the subject of the diploma, convertibility shows the applicability of the knowledge acquired during the training at work. Based on the results, the scientific fields were grouped according to convertibility and substitutability. The results show that a degree in business, IT, technical, law enforcement, medical and health sciences, as well as educational sciences increases the likelihood of both vertical and horizontal matching. A degree in social sciences and natural sciences increases the probability of horizontal incongruence. According to substitutability and convertibility graduates in different academic fields are classified in four groups (2 × 2 matrix).